INNOVATIVE CAPACITY MANAGEMENT MECHANISMS OF FOOD INDUSTRY ENTERPRISES IN REGIONAL ECONOMIC DEVELOPMENT (Marketing Journal, 2025)
This article highlights the theoretical and practical aspects of managing the innovation potential of food industry enterprises within the context of regional economic development . The study substantiates that the food industry is one of the key sectors of the regional economy , and its innovation activity directly affects regional competitiveness , employment , and the growth of added value . The mechanisms for managing innovation potential are analyzed in terms of their structural components , including the institutional environment , financial incentives , technological modernization , human capital , and the coherence of managerial decisions . Additionally , the article assesses the effectiveness of support tools for food industry enterprises in implementing innovation policy at the regional level . The research results serve as a scientific and practical foundation for developing regional development strategies and improving innovation management mechanisms in the food industry .
Keywords: regional economy; economic development; food industry; innovation potential; innovation activity; management mechanisms; competitiveness; institutional environment; technological modernization; human capital